PROBLEMS OF TRANSLATING ENGLISH PROVERBS INTO UZBEK - Ranokhon Oktamboyeva Khasan kizi (Ta'lim innovatsiyasi va integratsiyasi, 2023)
Abstract: this work is devoted to investigate the study of proverbs in Uzbek and English languages through various aspects, mainly, identifying ways of translation and exact translations in both target languages.